Statistical optimization of ethanol-based biodiesel production from sludge palm oil using locally produced candida cylindracea lipase - Nasaruddin, Ricca Rahman; Alam, Md Zahangir; Jami, Mohammed Saedi; Salihu, Aliyu (Springer Netherlands, 2016)
Face centered central composite design was used to optimize the enzyme loading, reaction temperature and mixing speed of sludge palm oil (SPO) transesterification reaction using locally produced Candida cylindracea lipase. The developed quadratic model was found to be significant at p < 0.05. The highest biodiesel yield of 57.5 % (w/w SPO) and 15.22 % free fatty acids (FFA) conversion to biodiesel with coefficient of determination R2 of 0.91 and 0.93, respectively were obtained at enzyme loading of 0.4 U/g SPO, 41 °C and 250 rpm mixing speed. Enzyme loading (U/g) gave little effect on the %FFA conversion to biodiesel and total biodiesel yield compared to temperature and mixing speed due to high FFA and water content, thus further studies are required for improvement. The study shows the low cost SPO and locally produced lipase have a promising potential in the utilization of waste for low cost biodiesel production.